(untitled) (Fiep Bulletin - online, 2014)
The present study evaluated in practice the effect of weight training as a weight-loss factor, aiming to analyze if the resistance training has been effective in altering body composition in female individuals. Materials and methods: a field research, experimental and quantitative, with data obtained by measurement of skinfolds in a group with 13 participants with age range between 18 and 30 years of an Academy in Campo Grande-MS. results and discussions: the analysis of the collected data was possible to verify that there has been a significant reduction in the composition and maintenance of body weight.